NARASI DALAM CERITA BERGAMBAR UNTUK PAUD/TK (Kajian terhadap Muatan Nilai Personal dan Edukatif) - Umar Sidik (Sunan Kalijaga State Islamic University Yogyakarta, 2012)
The aim of this research is to describe the personal and educational values in the graphic stories of the learning materials for pre-school education/kindergarten. The research applies Huck et al’s theory (1987) which states that children stories are full of personal and educational values. The population of the research is graphic stories found in different sources for the materials of the pre-school education/kindergarten. The sampling method is purposive sampling, i.e. the sampling which is based on the research objective. The examination is conducted using extrinsic approach in order to emphasize the analysis on the values and functions of the stories. The analysis is carried out by establishing categories, describing, and drawing inferences. The result of the research shows that there are eleven values in the graphic stories of the materials of the preschool educations/kindergartens, i.e. the development of emotional, intellectual, imaginative (and fantasy), social, ethical and religious values; exploration and discovery; language acquisition; cultivation of sense of beauty, introduction to multicultural insights, development of reading habits, and building up good personality.